2019
DOI: 10.34019/2596-3325.2019.v20.24778
|View full text |Cite
|
Sign up to set email alerts
|

Animais peçonhentos do estado do Piauí: epidemiologia dos acidentes e lista de espécies de importância médica

Abstract: Cases of poisoning have increased considerably in Brazil, however for state of Piauí only two studies were carried out so far. Here, we investigated, through the notification forms, the epidemiological characteristics of cases of poisoning that occurred during 11 years in a macro-region of Picos, state of Piauí, Northeastern Brazil. Furthermore, we also check whether the species recorded in the notification forms correspond to the species that occur in the region. We recorded 1.249 cases of envenomations, bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this study, it was observed that most accidents were caused by scorpions, followed by snakes. Likewise, two different studies conducted by Cantinho et al from 2007 to 2014 and by Benício et al from 1999 to 2010 on accidents across different regions of the State of Piauí, revealed a remarkable incidence of scorpion-related accidents, followed by snakes [21,22] . In a study in the city of Palmas, Brazil, it was also observed a higher frequency of reported accidents caused by scorpions and snakes [23] .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, it was observed that most accidents were caused by scorpions, followed by snakes. Likewise, two different studies conducted by Cantinho et al from 2007 to 2014 and by Benício et al from 1999 to 2010 on accidents across different regions of the State of Piauí, revealed a remarkable incidence of scorpion-related accidents, followed by snakes [21,22] . In a study in the city of Palmas, Brazil, it was also observed a higher frequency of reported accidents caused by scorpions and snakes [23] .…”
Section: Discussionmentioning
confidence: 98%